Enhancing Local Government Financial Performance: The Roles of Own Revenue, Fiscal Balances, and Capital Investment - Teddy Saputra; Nyayu Fadilah Fabiany; Erny Melina (Al Dzahab, 2026)
Purpose: This study aims to investigate how Own-Source Revenue, Fiscal Balances, and Capital Investment act as key fiscal determinants influencing the financial performance of local governments in Jambi Province over the period 2019–2023. Unlike conventional studies that merely examine variable correlations, this research emphasizes the functional roles of these fiscal components in shaping regional financial outcomes. Design/Methodology/Approach: A quantitative research design is employed using secondary data collected from the Annual Audit Reports of Regional Government Financial Statements issued by the Audit Board of the Republic of Indonesia (BPK) Representative Office in Jambi Province. The dataset spans five consecutive years, allowing for robust longitudinal analysis. Findings: The results indicate that Own-Source Revenue and Capital Investment exert statistically significant positive effects on local government financial performance. Fiscal Balances, while structurally important, do not show significant partial influence individually. Nonetheless, when analyzed jointly, the three fiscal variables collectively explain substantial variations in regional financial outcomes. Research Implications: The findings highlight that fiscal autonomy requires more than reliance on central transfers. Local governments must enhance their capacity to optimize internal revenue sources and strategically allocate capital expenditures to achieve efficient, accountable, and sustainable financial performance. Policy implications include prioritizing local revenue mobilization and performance-oriented spending to strengthen regional autonomy.